THE INFLUENCE OF CUSTOMER PERCEPTION AND PERCEIVED VALUE TOWARDS THE PURCHASE INTENTION: ANALYSIS ON CANNED FISH PRODUCTS - Keryn Kezia Valens Imanuela Nelwan; James D. D. Massie; Regina T. Saerang (Universitas Sam Ratulangi, 2024)
Business in the food sector, especially canned fish products are the choice of most people interest. The intense competition between canned fish products and regular fish products means that the company must develop a strategy that can attract and increase consumer buying interest. This research contains two independent variables. Namely Customer Perception (X1), Profit Value (X2) and consumer Purchase Intention (Y) as the dependent variable. This research uses a quantitative method by distributing questionnaires to 100 respondents as research samples and also to process data. The results of this research shoe that costumer perception and perceived value have a positive effect on consumer purchase intentions. Keyword: Consumer Perception, Perceived Value, Purchase Intention